Ultrasonic characterization of tissues in cardiology - FILIPCZYŃSKI, Leszek (Archives of Acoustics, 1983)
In order to analyse the possibility of the determination of the properties of soft tissues using ultrasonic (noninvasive) methods, a review was made of the basic physical properties characterizing acoustic wave propagation in these tissues (propagation velocity, attenuation, scattering). In a discussion of the results of "in vitro" investigations, it was shown that investigations of backscattering can be very significant for cardiological applications; the heart muscle with scars caused by an infarct is characterized by an increased pro-portion of collagen-rich connective tissue which has the value of the back-scattering coefficient greater by a factor of some dozens than that of normal muscle. This is related to the higher echographic visualizability of collagen than other soft tissues and suggests the practical possibility of noninvasive distinguishing of the regions of the muscle with scars caused by the infarct from normal muscle. This possibility was confirmed by "in vivo" investigations performed on dogs by the method of grey level histograms obtained from ultrasonograms of dog's hearts.This paper has the character of a review.